Encyclopedia of birds: The comprehensive illustrated guide by international experts (Academic Press, 1998)
The book, with more than 200 magnificent color photographs and 150 carefully researched illustrations, maps, and diagrams, presents an up-to-date and comprehensive survey of the natural history of birds. It provides new conservation information on each order, using symbols to denote the three levels of threat - critically endangered, endangered, and vulnerable